Knowledge and attitude of married men towards vasectomy in an urban slum of Navi Mumbai - Nair, Ganesh R.; Wadke, Rishikesh; Relwani, Nisha; Mahadik, Virendra; Anjenaya, Seema (International Journal Of Community Medicine And Public Health, 2017)
Background: India’s total fertility rate has been 2.2 in 2016, which is not far from replacement levels of 2.1. Tubectomy has been able to achieve this to a good extent, however vasectomy which is a far safer and effective method, isn’t still popular amongst men due to gender bias in our country. This study intends to understand the reasons for gap in the demand for vasectomy. The objective was to assess knowledge and attitude of married men towards vasectomy. Methods: A descriptive cross sectional study was carried out amongst 121 married men selected by simple random sampling, in the age group of 21 to 50 years and who hadn’t undergone vasectomy. A pretested structured questionnaire was used to assess knowledge. Respondents’ attitude was measured on 4 point Likert’s scale. Data was analysed using SPSS software version 21. Results: 70.2% men were aware of vasectomy. Main sources of information were mass media (42.35%), family and friends (29.41%) and doctors (24.7%). 47.1% of respondents felt that men should not undergo vasectomy. The main reasons given for disapproval were “women are best suited for sterilization procedure” (68.42%), “Vasectomy can make men impotent”(14.03%), “Leads to general weakness and blood loss” (13.03%), “Can’t do heavy work” (11.5%) and “Fear of surgery”(5.7%). Only 16.5% men agreed that vasectomy is better than tubectomy. Conclusions: In our country there is a clear gender bias towards tubectomy as men are reluctant to undergo vasectomy. Thus there is an urgent need to intensify the behavioural change communication approach which will enable to improve knowledge and change men’s attitude towards vasectomy.